Long-term stability of intra-oral maxillary distraction in unilateral cleft lip and palate: a case report. - (:unkn) unknown (My University, 2013)
This case report presents short and long-term treatment results of a unilateral cleft lip and palate patient treated with a modified intra-oral tooth-bone borne distraction appliance. The chief complaints of a 16 year-old, unilateral cleft lip and palate patient were poor facial aesthetics, crowding and a fistula. Severe maxillary retrognathism was treated via distraction osteogenesis of the maxilla and performed using an intra-oral tooth-bone borne appliance. Treatment continued to completion with a multibracket system. At an eight-year review following the distraction procedure, the short and long-term results were determined cephalometrically. Following the distraction, A-point advanced 7 mm, 2 mm of which relapsed during fixed appliance treatment. At the end of the active treatment, the patient's skeletal and dental Class III relationship improved to Class I, which was preserved at the long-term review. The profile was markedly improved by the distraction osteogenesis. In cases of severe maxillary retrognathism as a result of a cleft lip and palate, maxillary distraction osteogenesis provides a viable alternative to orthognathic surgery.